2009
DOI: 10.1258/rsmmsl.49.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of firearm mortalities in the Niger Delta region of Nigeria: a study of 136 consecutive autopsies

Abstract: A prospective autopsy study of firearms-related death was carried out by the authors in the Niger Delta region of Nigeria. The purpose of the study was to evaluate the pattern, frequency, and anatomical sites of wounds, also the cause of death and the age and sex distribution of victims. The autopsies were performed after being served with the coroner's inquest forms. In all cases standard autopsy procedures were adopted and reports issued. A total of 136 consecutive firearm deaths were autopsied. There were 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 13 publications
3
9
1
Order By: Relevance
“…Age influence: Youths in the age bracket 15 to 29 are not only perpetrators but also the major victims as evidenced by our findings and others [14]. Thus, the higher the populations in this age group in the society the higher the homicide rate.…”
Section: Similaritiessupporting
confidence: 72%
See 1 more Smart Citation
“…Age influence: Youths in the age bracket 15 to 29 are not only perpetrators but also the major victims as evidenced by our findings and others [14]. Thus, the higher the populations in this age group in the society the higher the homicide rate.…”
Section: Similaritiessupporting
confidence: 72%
“…With respect to periodic changes analysis of homicides in South Africa indicate that in the past two decades, knives and other stabbing weapons were used in the vast majority of colored people's murders, whereas currently, firearms are as likely to be used as knives [3]. In Nigeria most studies reported firearms as the most common weapon used in homicides [5][6][7][14][15][16], while others reported sharp piercing objects [17][18][19].…”
Section: Weapons Of Choicementioning
confidence: 99%
“…Firearm wounds were the largest cause of death, in a frequency close to other European countries, 23,26,27 lower than in the United States 7 and greater than in African countries. 25,28 The distribution of most parameters remained unchanged among people older than 15 years, with the exception of the cause of death. The decrease in homicide cases due to gunshot wounds could be explained by a restriction of firearm availability through more stringent legislation.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, injuries on and around the neck were nearly three times more frequent in femicide victims. Gunshots, especially to the head, are highly lethal 36 and tend to involve premeditated attacks, normally associated with illegal activities such as executions on orders from drug dealers 37,38 . In other studies on femicide, the neck was also one of most frequently affected areas 26 .…”
Section: Discussionmentioning
confidence: 99%